Modeling of influence of cooled and uncooled rolls on temperatures and stresses of the industrial ingot surface in the area of the secondary cooling - A. N. Chichko; D. M. Kukuj; N. V. Andrianov; Ju. V. Jatskevich; O. I. Chichko (Литьë и металлургия)
On the basis of the system “ProNRS-2'' there are carried out the computer calculations of tensile and compressive stresses along the length of the ingot of size 250x300 mm for the group of industrial steels. There is received the information about the stresses in ingots from the steel 40X, 70K, 2C45, 20C45, 20XH3A. There is shown, that the highest level of tensile stresses is observed for the ingot from the steel 40X, and the lowest — for the ingot from the steel 70K.